(3GdJMdjd GdGbJUGOj GdHjFjs - (3TJhM(B, (3hdjOs ((3YeGfs (3eQcR GdcJGH GdGcGOjejs, 2021)
(3jYJHQ gPG GdcJGH GdHjOGZhLj KeQI JOQjS ebjGS GbJUGO GdHjFI dYOI SfhGJ aj LGeYI Shb GgQGS GdLRGFQ, agh jMJhj Ydi SJI aUhd eJfGZeI, GP jHJOC HTQM bOQI GdShb Ydi GdJNUjU GdcaD ddehGQO GdGbJUGOjI hHGdJGdj JMbjb GbUi QaGgjI eecfI, Ke jhVM Gge MGdGJ GdaTd GdShbj hcjajI YLR LgGR GdKef Ydi GOQGc QaGgjI HGQjJh aj GdGSJgdGc hGdGfJGL eYG aj MVhQ gPg GdMGdGJ (B((3GdGMJcGQ, GdSdY GdYehejI, GdeYdheGJ ZjQ GdJGeI, GdGKGQ GdNGQLjI(B) (3eY GdJQcjR Ydi GdGKGQ GdNGQLjI GdSdHjI GdeJeKdI aj GdJdhK GdHjFj(B. (3hjMJhj gPG GdcJGH GjVG Ydi TQM eaUd decGfI GdeTcdI GdHjFjI aj GdacQ GdGbJUGOj GdJbdjOj hGdeYGUQ hCSdhH JMOjO MLe GdJdhK GdGeKd GLJeGYjG habG dWQjbI GdYGFO hGdJcdaI, hcPdc WQb JbOjQ hJbjje GdCVQGQ GdHjFjI GdJj jMOKgG GdfTGW GdGbJUGOj, hcPG Gge GOhGJ GdSjGSI GdHjFjI GdJj JJONd HgG GdSdWGJ GdYehejI dJNajV GdJdhK GdHjFj hGdeMGaXI Ydi GdHjFI, eY GMJhGAg aj GdCNjQ Ydi eYLe ddeUWdMGJ GdNGUI HYde GbJUGO GdHjFI(B.s
Keywords: (3GdEbJUGO GdHjFjs; (3GdJMdjd GdGbJUGOj (B- (3GdSjGSI GdHjFjI s